Prolactin Increases the Frequency of Follicular T Helper Cells with Enhanced IL21 Secretion and OX40 Expression in Lupus-Prone MRL/lpr Mice - Yolanda P. Alemán-García; Ricardo M. Vaquero-García; Rocio Flores-Fernández; Ezequiel M. Fuentes-Pananá; Patricia Gorocica-Rosete; Alberto Pizaña-Venegas; Luis Chávez-Sanchéz; Francico Blanco-Favela; María V. Legorreta-Haquet; Adriana K. Chávez-Rueda (Journal of Immunology Research, 2021)
Systemic lupus erythematosus is characterized by high levels of IgG class autoantibodies that contribute to the pathophysiology of the disease. The formation of these autoantibodies occurs in the germinal centers, where there is cooperation between follicular T helper cells (TFH) and autoreactive B cells. Prolactin has been reported to exacerbate the clinical manifestations of lupus by increasing autoantibody concentrations. The objective of this study was to characterize the participation of prolactin in the differentiation and activation of TFH cells, by performing in vivo and in vitro tests with lupus-prone mice, using flow cytometry and real-time PCR. We found that TFH cells express the long isoform of the prolactin receptor and promoted STAT3 phosphorylation. Receptor expression was higher in MRL/lpr mice and correlative with the manifestations of the disease. Although prolactin does not intervene in the differentiation of TFH cells, it does favor their activation by increasing the percentage of TFH OX40+ and TFH IL21+ cells, as well as leading to high serum concentrations of IL21. These results support a mechanism in which prolactin participates in the emergence of lupus by inducing overactive TFH cells and perhaps promoting dysfunctional germinal centers.